Modelling an Assembly Line Using Tecnomatix Plant Simulation Software - Afizul, Nur Asyiqah; Pagan, N.A.; Ng, Khang Yinn (Research in Management of Technology and Business, 2024)
Industries operate under unyielding pressure to meet the escalating demands of customer orders. However, various configurations of production lines often lead to inefficiencies in productivity. Addressing this challenge, simulation techniques offer preliminary insights, crucially aiding in the early detection of potential bottlenecks. This study focuses on employing Tecnomatix plant simulation software to identify bottlenecks within existing furniture assembly lines. The findings of this investigation highlight a bottleneck in the taping process, significantly impacting line balancing. Through simulation, the study observed a substantial increase in throughput, from 358 to 1027 units, after some changes were made to the identified bottleneck. Insights gained from Tecnomatix plant simulation facilitate evidence-based decision-making, empowering the company to optimize production capacity effectively. By addressing identified bottlenecks, the company can enhance its ability to meet customer demands efficiently. This underscores the critical role of simulation tools in streamlining production processes and maximizing operational effectiveness. Ultimately, the findings highlight the importance of continually refining and adapting manufacturing operations to remain competitive in today’s demanding market landscape.